GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU BERBASIS TEKNOLOGI DI SDN 025282 BINJAI UATARA - Anggun Arditha; Natasya Sihombing; Winara; Wildansyah Lubis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research examines the leadership style of the Principal of SD Negeri 025282North Binjai in encouraging the digitalization of education amidst the technologicalcompetency gap between senior and young teachers. Using a descriptivequalitative approach, data was collected through in-depth interviews with threeinformants: School Principal, Senior Teacher, and Young Teacher. Data analysisuses the Miles, Huberman, and Saldana interactive model (data condensation,data presentation, conclusion drawing) with validity maintained through sourcetriangulation and member checking. Findings show the Principal combinestransformational and situational leadership styles contextually, emphasizingempathy, appreciation, and intergenerational collaboration. The two mainstrategies implemented are: (1) a Structured Peer Tutoring System formalizedthrough a Decree, placing young teachers as technical supervisors while seniorteachers share pedagogical expertise; and (2) the regular 'IT Clinic' program everyFriday specifically for senior teachers. Implementation of these two strategies iseffective in improving technology-based teacher performance. Qualitativequantitative results show that senior teachers are able to increase digitalindependence by around 60–70%, while young teachers experience increasedproductivity and learning innovation after the workload is reduced. In conclusion,leadership that is empathetic, appreciative and collaborative between generationsis the main driver of digital transformation at the elementary school level, and canbe used as a practical model for overcoming the intergenerational digital divide inthe primary education context.